Experimental investigation of the strength of anisotropic solids under biaxial loading oblique to the principal material directions - Josef Eberhardsteiner; Manfred Gingerl; Lubomir Ondris; Rudolf Beer (Communications - Scientific letters of the University of Zilina, 2000)
Realistic finite element ultimate load analyses of structural details as well as of shell structures made of anisotropic materials require suitable constitutive equations for the prediction of the deformational behavior and ultimate strength of biaxially loaded solids. However, there is a lack of adequate biaxial experimental data, particularly if loading situations are considered where the principal loading directions do not coincide with the principal material directions.From the theoretical point of view one has to obey the stress-strain relationship. There is no principal difference in dealing with different kinds of anisotropic materials, such as biological tissues (human skin), anisotropic rubbers, woven fabrics (textures), reinforced polymers and any kind of plastic deformed membranes. However, the design of the experiment, the construction of the loading device and the loading procedure are strongly influenced by the shape and size of the test specimen available (or in view to the goal of the investigation necessary) and by the mechanical properties of the material under consideration.In this paper the development of an adequate testing device as well as a testing specimen is shown for the case of orthotropic wood. The goals of this investigation are the determination of the material strength and the biaxial stress-strain relationship of wood when loaded oblique to the grain direction.